AI Enabled Ensemble Deep Learning Method for Automated Sensing and Quantification of DNA Damage in Comet Assay. (1st March 2023) - Mehta, Prateek; Namuduri, Srikanth; Barbe, Lise; Lam, Stephanie; Faghihmonzavi, Zohreh; Kamat, Vivek; Finkbeiner, Steven; Bhansali, Shekhar
Abstract : Comet assay is a widely used technique to assess and quantify DNA damage in individual cells. Recently, researchers have applied various deep learning techniques to automate the analysis of comet assay. Image analysis using deep learning allows combining multiple parameters of images and performing computation at a pixel level to provide quantifiable information about the comets. The current deep learning analysis algorithms use a single neural network as a standard method, which relies on many comet images and prone to high variance in predictions. Here, we propose a new ensemble model consisting of a collection of deep learning networks with different configurations and different initial random weights trained on the same dataset to calculate one weighted prediction for DNA damage quantification. To develop this model, we curated a trainable comet assay image dataset consisting of1309 images with 9204 extracted features of cell head and tail length, area, etc With the proposed method we could achieve significantly higher accuracy (R2 = 89.3%, compared to 74% with the standard single neural network as reported in data published by M. D. Zeiler and R Fergus (European conference on computer vision, pp. 818–833 2014). Furthermore, deep regression with the proposed architecture produced much more reliable and accurate results than conventional method.